Electrothermal Vessel Sealing a Time Saving Alternative to Classic Suturing in Total Abdominal Hysterectomy; A Retrospective Study - Zohra, Sadaf; Firdos Chohan, Shazia; Najeeb, Wajeha; Komal, Naima; Mohsin, Rabia; Islam, Abida (Pakistan Armed Forces Medical Journal, 2024)
ABSTRACT Objective: To analyze efficacy of Electrothermal Vessel Sealing in comparison to Conventional Suture Ligation in Total Abdominal Hysterectomy. Study Design: Quasi-experimental study Place and Duration of Study: Department of Obstetrics and Gynecology, Pakistan Emirates Military Hospital Rawalpindi, Pakistan from Aug 2022 to Aug 2023. Methodology: The quasi-experimental study included one hundred and sixty six participants divided into two groups, Group-I had 83 patients while 83 patients were placed in group-II. Group-I received Ligasure and group-II received conventional suturing while undergoing total abdominal hysterectomy. Primary outcomes included estimated blood loss, pedicle securing time, surgery duration, post-operative NPO and hospital stay. Secondary outcomes involved need for suture ligation in surgeries with Ligasure. Results: Median age was for group I was 49(7) for Ligasure and 48(5) for conventional suture. Both groups had median BMI of 25(4) and median parity of 4(1). In the Ligasure group, 58(69.9%) participants had TAH, and 25 (30.1%) had TAH and BSO, while in the conventional suture group, 63(75.9%) had TAH and 20(24.1%) had TAH plus BSO. In the Ligasure group, 49.4% of the participants had AUB as the most common indication, whereas in the conventional suture group, 42.2% had leiomyoma. Notably, there was significantly lower blood loss with Ligasure (90 vs. 200 ml, p-value 0.001), as well as a shorter duration of surgery (35 min vs. 65 min, p-valu Conclusion: Ligasure was found to be advantageous over conventional suture in terms of perioperative surgical outcomes for total abdominal hystrectomy.